Treatment of bauxite residues - acidic leaching (first part) - Stopić, Srećko R.; Damjanović, Vladimir; Filipović, Radislav; Kamara, Mary D.; Friedrich, Bernd G. (Vojnotehnički glasnik / Military Technical Courier, 2023)
Introduction/purpose: Bauxite residue as a waste product from the aluminium industry produced through the Bayer process is mainly composed of iron oxide, titanium oxide, silicon oxide and undissolved alumina together with a wide range of other oxides and a minor content of rare earth elements, gallium, vanadium and scandium, which vary according to the country of origin of the bauxite. The extraction of valuable elements from bauxite residues and the minimisation of bauxite residues during different treatments are an open research field. Methods: Different hydrometallurgical and pyrometallurgical methods were used for the treatment of bauxite residues. In this study, the results of the hydrometallurgical treatment of bauxite residue from Alumina Zvornik using sulfuric acid and hydrochloric acid will be shown in order to study the change of the mineralogical composition. Leaching efficiency will be calculated using the ICP OES analysis. The XRD-Analysis was used for the characterization of the initial material and solid residues studying the change of the mineralogical phases. Results: Leaching of bauxite residues with sulphuric and hydrochloric acid leads partially to the change of mineralogical structure and the transfer of elements into a liquid phase. Natural precipitation of iron is observed over time. Silica gel formation is confirmed during leaching of bauxite residues with hydrochloric acid. Conclusion: A new research strategy for treating bauxite residue is needed in order to ensure a complete change of the initial minearlogical structure and the most efficient transfer of metals into a liquid phase.